Replacing rice straw with peanut vine and Broussonetia papyrifera silage in beef cattle feed reduced the use of soybean meal - Xin Yi; Yueming Li; Yue Liu; Minzhe Zhang; Zhenming Zhou; Qingxiang Meng; Hao Wu (Animal Nutrition)
The present study investigated whether replacing dietary rice straw with peanut vine (PEV) and Broussonetia papyrifera silage (BPS) reduces the use of soybean meal and explored its effects on the growth performance, blood biochemical indicators, serum metabolomics, and meat quality of fattening bulls. Forty-five Simmental crossbred bulls (initial body weight = 484.29 ± 8.49 kg) were randomly allotted into three dietary treatment groups (n = 15): (1) CON, 5% rice straw (DM basis); (2) PEV, 5% peanut vine (DM basis); and (3) BPS, 5% B. papyrifera silage (DM basis). The remaining roughage for all three treatment groups was supplemented with 25% corn silage (DM basis). The experiment lasted for 123 d, with the first 14 d serving as an adaptive period. Throughout the experiment, dietary BPS decreased the average daily dry matter intake (P < 0.001) and feed cost (P < 0.001). Serum metabolomics analysis showed that PEV affected the phenylalanine, tyrosine, and tryptophan biosynthesis pathways (P = 0.021) and lysine degradation pathway (P = 0.042), whereas BPS affected the phenylalanine, tyrosine and tryptophan biosynthesis pathways (P = 0.004), lysine degradation pathway (P = 0.012), and serotonergic synapse pathway (P < 0.001). Regarding meat quality, the redness (P = 0.025) and hue angle values (P < 0.001) of the longissimus dorsi muscle were lower in the BPS group than in the CON and PEV groups. The yellowness of the longissimus dorsi muscle was lower in the BPS group than in the PEV group (P = 0.024), and the shear force was lower in the PEV group than in the BPS group (P = 0.014). However, lysine content in beef was higher in the BPS group than in the CON group (P = 0.005). In conclusion, replacing rice straw with PEV and BPS reduced the use of soybean meal but had no adverse effects on growth performance. BPS affected the amino acid metabolism of bulls, thus decreasing feed intake and increasing the lysine content in meat. The PEV group showed better meat quality than the BPS group.